PENGARUH KOMPETENSI PEDAGOGIK GURU TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI KELAS XI DAN XII MIA SMA MUHAMMADIYAH 1 PEKANBARU - Rosi, Tivani Citra; Nas, Syakdanur; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack : This study aims to determine the influence of teacher pedagogic competence on student learning outcomes economic subjects class XI and XII MIA SMA Muhammadiyah 1 Pekanbaru. Population in this study were students of class XI and XII MIA SMA Muhammadiyah 1 Pekanbaru as many as 259 students, and the sample of 67 students. Measurement of data using the question form and documentation. Analysis of data used is simple linear regression. The result of research based on simple linear regression showed teacher pedagogic competence influence to student learning result of economy in class XI and XII MIA SMA Muhammadiyah 1 Pekanbaru,this can be seen from constant value (a) equal to 36.575 and regression coefficient value (b) equal to 0.953 with regression equation 36.575+0.953. Seen from the calculation of R2 (R Square Change) obtained the value of 0.781. Means that the contribution of teacher pedagogic competence influence on student learning outcomes of 78.1%..Key word : Teacher Pedagogic Competence, student learning outcomes